THE ROLE OF REGIONAL DISASTER MANAGEMENT AGENCIES IN NATURAL DISASTER MITIGATION IN CIANJUR DISTRICT - Neng Sita Novianti; Tuah Nur; M. Rijal Amirulloh (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
To reduce the high impact of disaster risk, BPBD Cianjur Regency has made several efforts, one of which is the pre-disaster stage, namely disaster mitigation. This research aims to analyze natural disasters that often occur in Cianjur Regency and the need for natural disaster mitigation measures in order to minimize the risk or impact caused. The theory used in this research is the role theory proposed by Haroepoetri Arimbi and Santosa (2003). The result of this research is that BPBD Cianjur Regency in the implementation of natural disaster mitigation focuses on non-structural mitigation by running several programs. Overall, the implementation of the mitigation program has been running well but has not been maximized due to the limited budget and the vast area of Cianjur Regency, making it difficult for BPBD to run and develop natural disaster mitigation programs in all areas of Cianjur Regency.